2001
DOI: 10.1080/00420980126673
|View full text |Cite
|
Sign up to set email alerts
|

Energy Trade-offs and Market Responses in Transport and Residential Land-use Patterns: Promoting Sustainable Development Policy

Abstract: Sustainable development policy is examined for the Belfast Metropolitan Area using a range of linked aggregate and disaggregate models. Energy trade-offs were modelled for both 'stationary' private dwellings and 'mobile' traffic-related energy sources. The research suggests that land-use policies, and in particular corridor-based densification linked to improved public transport, can achieve very significant reductions in mobile energy consumption and modest reductions in stationary energy use linked to reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…He concluded that relatively high housing densities can be achieved before any negative impacts due to solar exclusion become significant. Other modelling studies have previously shown a significant influence of built form on the energy used for heating and cooling in houses, with denser dwelling forms requiring less energy (Loder and Bayly et al, 1993;Cooper et al, 2001).…”
Section: Contextmentioning
confidence: 97%
“…He concluded that relatively high housing densities can be achieved before any negative impacts due to solar exclusion become significant. Other modelling studies have previously shown a significant influence of built form on the energy used for heating and cooling in houses, with denser dwelling forms requiring less energy (Loder and Bayly et al, 1993;Cooper et al, 2001).…”
Section: Contextmentioning
confidence: 97%
“…The majority of this research focuses on studies of housing and neighborhood choice (e.g. Cooper, Ryley, & Smyth, 2001;Earnhart, 2001;Hunt, McMillan, & Abraham, 1994;Hunt, 2001;Jansen et al, 2009;Kim, Pagliara, & Preston, 2005;Molin, Oppewal, & Timmermans, 1997;Molin, Oppewal, & Timmermans, 2000;Molin, Oppewal, & Timmermans, 2001;Phipps & Carter, 1984, 1985Senior, Webster, & Blank, 2006;Tayyaran et al, 2003;Walker, Marsh, Wardman, & Niner, 2002;van de Vyvere, Oppewal, & Timmermans, 1998). Others have considered just neighborhood choice (e.g.…”
Section: Conjoint and Discrete Choice Experiments Of Housing And Neigmentioning
confidence: 98%
“…Many researchers have developed a different residential location choice model in order to analyze the demand of households for housing, transportation, and the living environment [27]. According to the economic theory, household residential choices are functions of different housing and location attributes that are differentiated by a variety of household characteristic [28].…”
Section: Introductionmentioning
confidence: 99%